Increased morbidity after circumcision from a hidden complication - Atikeler, MK; Onur, R; Gecit, I; Senol, FA; Cobanoglu, B (Blackwell Publishing Ltd, 2001)
Objective To describe a late complication of circumcision and to elucidate the role of surgical materials or any foreign body in the development of a subcutaneous mass in circumcised boys. Patients and methods From May 1998 to March 2001, 646 boys were circumcised and 523 (mean age 6.5 years, range 0-13) re-examined for the possible development of a subcutaneous mass. Twenty-six (5%) of the re-examined patients had such a mass under the penile skin; it was removed in all patients under local anaesthesia and examined histopathologically. Results The mean (SD, range) delay after circumcision before developing or detecting the mass was 3.2 (0.7, 1-7) months. All patients were asymptomatic but there was purulent discharge in four. On removing the mass, histopathology showed the development of granulation tissue with foreign-body giant cells. Conclusion There may be minor complications after circumcision which cannot be avoided even when the procedure is undertaken by surgeons. Awareness of such complications occurring long after circumcision may aid in the early detection of this asymptomatic mass and prevent a more severe outcome.
Keywords: circumcision; subcutaneous mass; late complication; granulation tissue